Definition of a measurement technique for hexapod circular smart fixators' perioperative assembly parameters and investigation of alignment and correlation with postoperative measurements: a retrospective cohort study - Muharrem Kanar; Yusuf Sülek; Tolga Hayrettin Seymenoğlu; Raffi Armağan (BMC Musculoskeletal Disorders)
Abstract Background With the assistance of smart fixator technologies, the correction of complex deformities has been facilitated; however, the accurate integration of specialized radiographs and measurements into the system remains the greatest disadvantage, necessitating specialized imaging and an experienced team. When inexperienced technicians and doctors perform these specialized postoperative radiographs, excessive exposure of the patient and team to radioactive rays exacerbates inadequacies in measurements and delays the correction of residual deformities due to angular and translational adjustments. In this study, we compared postoperative measurements with those taken peroperatively via fluoroscopy, hypothesizing that it reduces the exposure of the patient and team to radioactive rays, allows for more accurate and timely correction of deformities and assembly parameters, and reduces time and costs. Methods Between 2013 and 2022, 84 patients with bone deformities were retrospectively reviewed. All patients had bone deformities and were treated with computer-assisted circular external fixator systems (Ca-CEF). Assembly parameter measurements began to be corrected via artificial neural network software via peroperative fluoroscopy in 37 patients and postoperative radiography in 47 patients. The surgical duration for all patients, peroperative measurement values, and number of radiographs taken on postoperative day 1, week, and month until deformity correction were recorded. Results The duration until deformity correction was shorter in patients who underwent postoperative measurements (mean 50.24 days) than in those who underwent peroperative measurements (mean 42.31 days), but this difference was not statistically significant (p = 0.102). The surgical duration was significantly shorter in patients with postoperative measurements (mean of 130.37 min) than in those with peroperative measurements (mean of 155.88 min) (p = 0.045). For patients with postoperative measurements, 56.04 postoperative radiographs were taken. In contrast, patients with peroperative measurements had fewer radiographs totaling 28.7. This difference was statistically significant (p < 0.01). There was no statistically significant difference in the fluoroscopy dose between patients with postoperative measurements (mean 18.54 mGy) and those with peroperative measurements (mean 22.22 mGy) (p = 0.105). Conclusion To achieve accurate assembly parameters, minimizing X-ray exposure is crucial but can pose challenges. Our results showed that despite an average increase of 25 min in surgical duration, the time taken for deformity correction was shorter. Additionally, we obtained fewer postoperative radiographs, indicating reduced radiation exposure.